Flexural, Dynamic and Thermo-Mechanical Analysis of Pineapple Leaf Fiber/Epoxy Composites. Issue 17 (2nd December 2022) - Najeeb, M.I.; Sultan, M.T.H.; Shah, A.U.M.; Safri, S.N.A.; Jawaid, M.; Abu Talib, A.R.; Basri, A.A.
ABSTRACT: The properties of pineapple leaf fiber composites drawn from the vastly untapped Yankee pineapple plant variant were tested in this study. The properties of silane treated ( T -PALFC) and untreated (UT-PALFC) samples were evaluated using flexural testing, dynamic mechanical analysis (DMA), and thermomechanical analysis (TMA). In this study, the T-PALFC sample was specifically treated in silane for 3 hours. The results show that the bending strength is improved by up to 97% in PALF composite compared to epoxy composite.The DMA results show that the UT-PALFC possess 7.1% higher storage modulus than T-PALFC, indicating untreated fiber attribute to high dynamic property in composite. The TMA finding shows the sequence of linear coefficient of thermal expansion (CTE) as follows: T-PALFC > Neat epoxy > UT-PALFC. Furthermore, this research shows T-PALFC displayed lower properties compared to UT-PALFC because the composite had low cross-linked network. This is because T-PALFC had low glass transition temperature, Tg as shown in tan delta curve and was further supported in differential scanning calorimetry analysis. Moreover, morphological analysis of the cross-section image of the T-PALFC shows the existence of a wide gap between the PALF and the matrix compared to UT-PALFC. Graphical abstract: uf0001